Analysis of personality disorder profiles obtained by five-factor personality model - Pešić, Danilo; Adžić, Tara; Vuković, Olivera; Kalanj, Marko; Lečić Toševski, Dušica (Vojnosanitetski pregled, 2021)
Background/Aim. In spite of the growing body of evidence in the field of personality disorders, these disorders still retain the lowest diagnostic reliability of any major category of mental disorders. The aim of this study was to investigate the differences of personality profiles in patients diagnosed with personality disorder in comparison with the group of healthy control subjects, as well as to establish to what extent the five-factor personality model domains determine the specific clusters of personality disorders. Methods. The study group comprised 97 patients diagnosed as personality disorders (according to the Diagnostic and Statistical Manual of Mental Disorders – DSM-IV criteria), aged between 18 and 65 years [mean = 35.78 years, standard deviation (SD) = 13.72 years], 67% were female. Control group included 58 healthy subjects (student population) aged between 20 to 35 years (mean = 22.48 years, SD = 2.56 years), 56% were female. The assessment was carried out by the new version of the NEO Personality Inventory-Revised (NEO-PI-R), form S, and the Structured Clinical Interview (SCID II) for DSM-IV disorders. Results. The three clusters were found by the use of regression analysis: cluster A – eccentrics (low scores in agreeableness), cluster B – dramatics (high score in extroversion, low score in agreeableness, and cluster C – anxious (low score in extroversion). The findings showed that the high level of neuroticism was a non-specific predictor of all three clusters, while dimension openness to experience had no predictive power for any of the three clusters. Conclusion. Our findings support the meta-analysis which suggests consistently high level of neuroticism and low level of agreeableness in most personality disorders. The study showed that it is possible to conceptualize personality disorders by using five-factor personality model of normal personality. Integrating the psychiatric classification with the dimensional model of general personality structure could enable the uncovering of essential parameters for setting the diagnosis.
Keywords: personality disorders; personality assessment; neuroticism; surveys and questionnaires